2019
DOI: 10.3390/bios9020051
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Toolkit for Characterizing the Mechanical and Electrical Properties of Engineered Neural Tissues

Abstract: We have designed and validated a set of robust and non-toxic protocols for directly evaluating the properties of engineered neural tissue. These protocols characterize the mechanical properties of engineered neural tissues and measure their electrophysical activity. The protocols obtain elastic moduli of very soft fibrin hydrogel scaffolds and voltage readings from motor neuron cultures. Neurons require soft substrates to differentiate and mature, however measuring the elastic moduli of soft substrates remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 35 publications
(44 reference statements)
0
31
0
Order By: Relevance
“…The indention method consistently produced robust measurements, which indicated that the white matter tissue was approximately one third stiffer than gray matter tissue. These studies validated the use of indentation methods to interpret the mechanical properties of neural tissues [19,21,23,26,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…The indention method consistently produced robust measurements, which indicated that the white matter tissue was approximately one third stiffer than gray matter tissue. These studies validated the use of indentation methods to interpret the mechanical properties of neural tissues [19,21,23,26,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 55%
“…The mechanical integrity and stability of engineered tissues depend upon the hydrogel-based bioinks used during fabrication. The adjustable concentration of biomaterials can appropriately tune the mechanical and rheological properties of hydrogels [19]. It is important to understand the effect of mechanical environment on neurite outgrowth for understanding neural tissue regeneration strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from commercial fibrin hydrogels products [49,69], the isolation and purification of autologous plasma can also prepare fibrin hydrogels commonly used in neural tissue engineering. However, the cost is only materials, without traffic expense and patent fee [70].…”
Section: The Synthesis and Modification Of Fibrin Hydrogelsmentioning
confidence: 99%